2023
DOI: 10.1097/mpg.0000000000003751
|View full text |Cite
|
Sign up to set email alerts
|

Practice Survey: Depression Screening in Pediatric Inflammatory Bowel Disease

Abstract: Background:Little is known about depression screening practices in pediatric inflammatory bowel disease (IBD) care. This study summarizes depression screening within IBD centers in the ImproveCareNow Collaborative Network. Methods: Pediatric IBD providers across 79 IBD centers completed an online survey on current practices surrounding depression screening. Results: Half of centers report doing annual depression screening, largely for patients 12-14 years. The Patient Health Questionnaire (PHQ-9) is most often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, the CEDNA study only collected data on diagnosed mental disorders, not on mental abnormalities. Other studies have also found an association between PIBD, depressive disorders, and quality of life [37,38]. Patients with PIBD have a 50% increased risk of developing depression [39].…”
Section: Discussionmentioning
confidence: 89%
“…However, the CEDNA study only collected data on diagnosed mental disorders, not on mental abnormalities. Other studies have also found an association between PIBD, depressive disorders, and quality of life [37,38]. Patients with PIBD have a 50% increased risk of developing depression [39].…”
Section: Discussionmentioning
confidence: 89%